Ekonomi Kreatif Berbasis Digital dalam Pengembangan Strategi Bisnis Perak dan Songket Ungga Menuju Industri 4.0 - Lilik Hidayati; Adi Irawan; Dwi Agustini; Pahmi Husain (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This community service activity aims to develop a digital business strategy for silver craftsmen and songket weavers in Ungga Village, Central Lombok, as an effort to increase the competitiveness of MSMEs in the Industry 4.0 era. The program is carried out using a participatory and collaborative approach, involving 20 local business actors through four main stages: 1) observation and mapping of business potential; 2) digital literacy and online marketing training; 3) assistance in the implementation of digital strategies; and 4) evaluation and reflection on the results of activities. Training materials include creative content creation, product branding, social media management, and data-driven marketing. The results of the activity showed an increase in participants' digital skills, characterized by the ability to manage business accounts on social media and marketplaces independently. The implementation of digital marketing strategies also has an impact on increasing average sales by 30%. The Ungga Digital Creative community was also formed as a forum for collaboration and sustainability of the digital-based creative economy ecosystem. Overall, this program is an integrative model of MSME mentoring, combining technology literacy, digital marketing practices, and strengthening community networks.